2022
DOI: 10.20882/adicciones.1646
|View full text |Cite
|
Sign up to set email alerts
|

Impacto del confinamiento en la conducta adictiva de los universitarios riojanos

Abstract: Impacto del confinamiento en la conducta adictiva de los universitarios riojanos Impact of lockdown on the addictive behavior of university students in La Rioja

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
1
2
0
2
Order By: Relevance
“…In the meantime, the authors state that the decrease in the consumption of these substances was related to the lockdown, which restricted social gatherings. It was also observed that students tend to consume substances in smaller quantities in the family environment, similar to what was found in this study ( 23 , 24 ) .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the meantime, the authors state that the decrease in the consumption of these substances was related to the lockdown, which restricted social gatherings. It was also observed that students tend to consume substances in smaller quantities in the family environment, similar to what was found in this study ( 23 , 24 ) .…”
Section: Discussionsupporting
confidence: 89%
“…Considering that the use of alcohol and other substances is associated with the practice of RSB, it was observed through the interviews that during the pandemic there was a reduction in the use of such substances, as in studies at Spanish ( 23 ) and Swedish ( 24 ) universities.…”
Section: Discussionmentioning
confidence: 99%
“…Considerando que o uso de álcool e outras substâncias estão associados com a prática de CSR, observou-se através das entrevistas que durante a pandemia houve redução no uso de tais substâncias, assim como em estudos em universidade espanhola (23) e sueca (24) .…”
Section: Discussionunclassified
“…Nesse ínterim, os autores afirmam que a diminuição no consumo dessas substâncias esteve relacionada com o lockdown, o qual restringiu as aglomerações sociais. Observou-se também que os estudantes tendem a consumir as substâncias em menor quantidade no ambiente familiar, semelhante ao encontrado nesta pesquisa (23,24) .…”
Section: Discussionunclassified
“…Although some studies on the impact of the pandemic on substance use among university students have been developed in Spain [ 31 , 32 ], to our knowledge this is the first study that includes a ten-year time course that focuses on cannabis use and exploring the lockdown time and the new normal period.…”
Section: Introductionmentioning
confidence: 99%